We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
54
1
avatar+74 

Let \($f(x)$\) and  \($g(x)$\) be polynomials.

Suppose $f(x)=0$ for exactly three values of  \($x$\): namely \($x=-3,4,$\) ,  and \($8$\).

Suppose \($g(x)=0$\) for exactly five values of \($x$\) : namely \($x=-5,-3,2,4,$\),  and $8$ .

Is it necessarily true that \($g(x)$\) is divisible by $f(x)$? If so, carefully explain why. If not, give an example where \($g(x)$\)  is not divisible by f(x).

Part 2:

Generalize: for arbitrary polynomials f(x) and g(x) , what do we need to know about the zeroes (including complex zeroes) of f(x) and g(x) to infer that g(x)  is divisible by f(x)?

 Apr 24, 2019

Best Answer 

 #1
avatar+101046 
+2

Next time make sure you delete all the meaningless $ signs.  So that your question presents properly.

 

\(\text{Let F(x) and G(x) be polynomials such that }\\ f(x)=F(x)(x+3)(x-4)(x-8)\\ g(x)=G(x)(x+3)(x-4)(x-8)(x+5)(x-2)\\ \frac{g(x)}{f(x)}=\frac{G(x)(x+3)(x-4)(x-8)(x+5)(x-2)}{F(x)(x+3)(x-4)(x-8)}\\ \frac{g(x)}{f(x)}=\frac{G(x)(x+5)(x-2)}{F(x)}\\ \)

 

g(x) is only divisable by f(x) if F(x) is a factor of G(x)(x+5)(x-2)

 

for instance in the following example g(x) is not divisable by f(x)


\(g(x)=7(x+5)(x-2)(x+3)(x-4)(x-8)\\ f(x)=(x^8+x^5-4x)(x+3)(x-4)(x-8)\\\)

.
 Apr 25, 2019
 #1
avatar+101046 
+2
Best Answer

Next time make sure you delete all the meaningless $ signs.  So that your question presents properly.

 

\(\text{Let F(x) and G(x) be polynomials such that }\\ f(x)=F(x)(x+3)(x-4)(x-8)\\ g(x)=G(x)(x+3)(x-4)(x-8)(x+5)(x-2)\\ \frac{g(x)}{f(x)}=\frac{G(x)(x+3)(x-4)(x-8)(x+5)(x-2)}{F(x)(x+3)(x-4)(x-8)}\\ \frac{g(x)}{f(x)}=\frac{G(x)(x+5)(x-2)}{F(x)}\\ \)

 

g(x) is only divisable by f(x) if F(x) is a factor of G(x)(x+5)(x-2)

 

for instance in the following example g(x) is not divisable by f(x)


\(g(x)=7(x+5)(x-2)(x+3)(x-4)(x-8)\\ f(x)=(x^8+x^5-4x)(x+3)(x-4)(x-8)\\\)

Melody Apr 25, 2019

11 Online Users